Preparation of a nanosilica cross‐linker and investigation of its effect on properties of guar gum fracturing fluid. (1st July 2017) - Zhang, Zifeng; Liu, Peisong; Pan, Hao; Zhao, Mengyun; Li, Xiaohong; Zhang, Zhijun
Abstract : The development of hydraulic fracturing has created a huge demand for fracturing fluids with high performance and low formation damage in recent years. A nanosilica cross‐linker precursor (NCP) was prepared by introducing boric acid to the surface of organic silica compound (C9 H23 NO3 Si, a silane coupling agent), the carrier. As‐obtained NCP was transformed into nanoparticles (NPs) with a diameter of 10–35 nm by self‐aggregation. The resultant NPs were used to crosslink low concentration of guar gum solution in order to improve the rheological and breaking properties of the fracturing fluid made of the NPs‐cross‐linked guar gum gels. Findings indicate that boric acid chemically reacts with the amino group of the silane coupling agent forming N–B bond via infrared analysis. The viscosity of NPs‐cross‐linked guar gum gels increases with the increase of particle size of NPs, which means that the particle size of NPs has a significant effect on the cross‐linking efficacy, the guar gum gels cross‐linked by a proper mass fractions of NPs exhibits good temperature resistance and shear resistance via rheometer. Moreover, the NPs‐cross‐linked guar gum gels possesses better breaking behaviour than the one cross‐linked by borate.